The The Effect of Electronic Word of Mouth on Purchasing Decisions for Shopee Products for Generation Z and Millenials in Bone Regency - Fitriani Arif; Muhammad Adli Alwi (IQTISHADUNA, 2023)
This study aims to determine the effect of Electronic Word of Mouth on product purchasing decisions at Shopee among Generation Z and Millennials in Bone Regency. This research uses a quantitative approach and descriptive-analytical. The data collection technique used in this study was distributing questionnaires to 50 respondents from the millennial and Z generations in Bone Regency. The data analysis technique is linear regression analysis. The study's findings that Electronic Word of Mouth has a positive and significant impact on consumer purchasing decisions. That is, the hypothesis is proven. Thus, the positive and significant influence shows that electronic word of mouth can be one of the considerations for generation Z and millennial generations in Bone Regency in deciding to buy products at Shopee.